A State of the Art Review For Removing Heavy Metals Resulting from Industrial Waste - Nyamiati, Retno Dwi; Setyaningtyas, Wiji Asih; Arstyanto, Dimas (PT FORMOSA CENDEKIA GLOBAL, 2024)
The contamination of heavy metals has become a serious concern for both the government and researchers due to industrial waste. Heavy metals possess toxic properties that can harm the human body if exposed over an extended period. It cannot be denied that toxic heavy metals come in various types, such as Ag (argentum), Cd (cadmium), Cr (chromium), Cu (cuprum), Ni (nickel), and others. In its development, various methods have been implemented to eliminate heavy metal waste, encompassing both conventional and modern approaches. Researchers are actively seeking the most efficient and effective method to address the issue of heavy metal removal. This review focuses on different methods for handling heavy metal waste, measuring the percentage of heavy metal loss to determine which method is the most effective and efficient in heavy metal removal.